2020
DOI: 10.14221/ajte.2020v45n8.5
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Crisis: Critical Events in the Mid-Career Stage

Abstract: To understand the ways in which teachers in the mid-career stage might be retained and maintained in the classroom and the profession, this article identifies the critical events in the journey of the mid-career teacher. The findings of a qualitative study that drew on narrative inquiry are used to explore the reasons why 20 mid-career teachers in Queensland, Australia, exited or remained in the classroom and/or profession. The article concludes with a profile of the mid-career teacher which helps to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The employees that have been surveyed for the research have shared how wrong career choices can cause feelings of un-fulfillment in their lives, the opinions of the participants can be seen to align with the research carried out by Cawte (2020), providing the employees with growth opportunities and other incentives can significantly increase the satisfaction level with the work, additionally, the organization can provide both intrinsic and extrinsic rewards to reduce the stress level of the employees. The participants have also agreed that wrong career paths often lead to dissatisfaction and low morale within the work environment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The employees that have been surveyed for the research have shared how wrong career choices can cause feelings of un-fulfillment in their lives, the opinions of the participants can be seen to align with the research carried out by Cawte (2020), providing the employees with growth opportunities and other incentives can significantly increase the satisfaction level with the work, additionally, the organization can provide both intrinsic and extrinsic rewards to reduce the stress level of the employees. The participants have also agreed that wrong career paths often lead to dissatisfaction and low morale within the work environment.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have also highlighted that people who go through this stage in their lives are also more focused on long-term goals and opportunities for future development. Recognition for the work done, and opportunities for growth and development are all factors that can influence the culture of the organisation and increase the job satisfaction of these individuals (Cawte, 2020). It has been found that both intrinsic and extrinsic factors help in reducing mid-career crises, while intrinsic factors such as relationships with co-workers and recognition is important, job and financial security are also important aspects which employees consider while deciding to continue with their profession.…”
Section: Literature Reviewmentioning
confidence: 99%